LncAABR07025387.1 Enhances Myocardial Ischemia/Reperfusion Injury Via miR-205/ACSL4-Mediated Ferroptosis - Sun, Weixin; Wu, Xiang; Yu, Peng; Zhang, Qian; Shen, Le; Chen, Jiandong; Tong, Huaqin; Fan, Manlu; Shi, Haibo; Chen, Xiaohu (Frontiers in Cell and Developmental Biology, 2022)
Ferroptosis is associated with the pathology of myocardial ischemia/reperfusion (MI/R) injury following myocardial infarction, which is a leading cause of death worldwide. Although long non-coding RNAs (lncRNAs) are known to regulate gene expression, their roles in MI/R-induced ferroptosis remain unclear. In this study, we explored the lncRNA expression profiles in a rat model of MI/R injury and found that the novel lncRNA, lncAABR07025387.1, was highly expressed in MI/R injured myocardial tissues and hypoxia/reoxygenation (H/R)-challenged myocardial cells. Silencing lncAABR07025387.1 improved MI/R injury in vivo and inhibited myocardial cell ferroptosis under H/R conditions. Bioinformatics analyses and luciferase, pull-down, and RNA-binding immunoprecipitation assays further revealed that lncAABR07025387.1 interacted with miR-205, which directly targeted ACSL4, a known contributor towards ferroptosis. Furthermore, downregulating miR-205 reversed the ACSL4 inhibition induced by silencing lncAABR07025387.1. These findings suggest that, mechanistically, lncAABR07025387.1 negatively regulates miR-205 expression and subsequently upregulates ACSL4-mediated ferroptosis. In conclusion, this study demonstrates that lncAABR07025387.1 acts as a competing endogenous RNA during MI/R injury and highlights the therapeutic potential of lncRNAs for treating myocardial injury.